"Multicultural Discourses in Turbulent Times" - Szabó, Helga (AMERICANA E-journal of American Studies in Hungary, 2022)
Multicultural Discourses in Turbulent Times Edited by Alexandra Cotoc, Octavian More and Mihaela Mudure Presa Universitara Clujeana, 2021 299 pages ISBN 9786063712616